Acting the Prince : Giacomo Joyce and Hamlet - Greer, Mick (2017)
Between November 1912 and February 1913, Joyce gave a series of 12 lectures on Hamletat the Università del Popolo, Trieste. Although these lectures are now lost, his extensive surviving notes suggest that the play was very much in his mind when he came to write Giacomo Joyce in 1914. Giacomo Joycesketches the obsession of an English teacher (who may or may not be entirely Joyce) for an unnamed female student in Trieste. Full of literary and, especially, theatrical allusions, Joyce’s last published work draws us into a search for the theatrical within the narrative as the nature of the protagonist’s relationship with his girl student is explored through juxtaposition with a range of allusions from the world stage. No textual “ghosts in the mirror”, however, are reflected more significantly in Giacomo Joyce than Hamlet. This article argues that Shakespeare not only provides Joyce with distorted verbal echoes and parallel events, but actually furnishes an underlying structure for Giacomo Joyce as a whole, through the Elizabethan 5 act structure. This structural adoption of a classic text to examine contemporary experience can be seen as paving the way for Ulysses, which had been in preparation for some time and on which Joyce was about to embark.